Integrated EpCAM‐independent subtraction enrichment and iFISH strategies to detect and classify disseminated and circulating tumors cells. Issue 1 (30th December 2015) - Lin, Peter Ping
Abstract: Application of tumor cell surface adhesion molecule EpCAM‐dependent antibody capture, and intracellular cytokeratins (CKs)‐dependent immunostaining strategies to detect disseminated or circulating tumor cells (DTCs or CTCs), is limited by highly heterogeneous and dynamic expression or absence of EpCAM and/or CKs in CTCs and DTCs, particularly in their capturing and identifying CTCs/DTCs shed from diverse types of solid tumor, thus being biased and restricted to the only both EpCAM and CK positive cancer cells. Moreover, heterogeneity of chromosome and tumor biomarker of CTCs/DTCs cannot be co‐examined by conventional CK/EpCAM‐dependent techniques. Accordingly, a novel integrated cellular and molecular approach of EpCAM‐independent subtraction enrichment (SE) and immunostaining‐FISH (iFISH ® ) has recently been successfully developed. SE‐iFISH ® is able to effectively enrich, comprehensively identify and characterize both large and small size non‐hematopoietic heteroploid CTCs, DTCs and circulating tumor microemboli in various biofluid specimens of either cancer patients or patient‐derived‐xenograft mice. Obtained tumor cells, free of anti‐EpCAM perturbing and hypotonic damage, are eligible for primary tumor cell culture as well as a series of downstream analyses. Highly heterogeneous CTCs and DTCs could be classified into subtypes by in situ phenotyping protein expression of various tumor biomarkers and karyotyping of chromosome aneuploidy performed by iFISH ® . Each CTC subtype may correlate with distinct clinical significance in terms of tumor metastasis, relapse, therapeutic drug sensitivity or resistance, respectively.